Respostas

2014-08-07T19:11:28-03:00
  vx= -b/2a   vy=-Delta/4a

A) h (x)=  - 2x + 8    V(1,7)
-(-2)/2.1
2/2
1    VX=1

delta= b²-4.a.c
delta=(2)² -4.1.8
delta=4 -32
delta=-28                        
 VY= -(-28)/4.1
 VY= 28/4
 Vy= 7  


B) i (x)= x² - 2x - 8  V(1,-9)
VX= 2/2
VX=1
delta= 4+32
delta=36
Vy= -36/4
Vy= -9

C) j (x)= x² + 2x - 3 V(-1,-4)
VX= -2/2
Vx= -1
delta 4+12
delta=16
Vy= -16/4
Vy= -4

D) k (x)= x² - 4x + 4 V(2,0)
VX= 4/2
Vx=2
delta=16-16
delta=0
Vy= -0/4
Vy=0

RESPOSTAS
A) V(1,7)
B) V(1,-9)
C)V(-1,-4)
D)V(2,0)

ESPERO TER AJUDADO!!!

2 4 2